Asperpentenone A, A novel polyketide isolated from the deep-sea derived fungus Aspergillus sp. SCSIO 41024. (February 2020) - Chen, Weihao; Liu, Haiyi; Long, Jieyi; Tao, Huaming; Lin, Xiuping; Liao, Shengrong; Yang, Bin; Zhou, Xuefeng; Liu, Yonghong; Wang, Junfeng
Graphical abstract: Highlights: A novel polyketide was isolated from the deep-sea derived fungus Aspergillus sp. SCSIO 41024. Extensive NMR spectroscopic analysis and X-ray crystallography data were used to elucidate the new structure. Kojic acid (3 ) and griseofamine A (9 ) exhibited weak antibacterial activities. Abstract: Asperpentenone A (1 ), a novel polyketide with a rare cyclopentenone-tetrahydrofuran moiety, was isolated along with eight known compounds (2 –9 ) from the deep-sea derived fungus Aspergillus sp. SCSIO 41024. Their structures including absolute configurations were determined by extensive analysis of their spectroscopic analysis and X-ray crystallography. Biological evaluation results revealed that kojic acid (3 ) showed weak antibacterial activities against Bacillus thuringiensis and Acinetobacter baumannii with MIC values of 32 and 128 μ g/mL, respectively. Furthermore, griseofamine A (9 ) exhibited weak antibacterial activity with an MIC value of 64 μ g/mL against Escherichia coli . The results of antibacterial experiments and especially the large yield of kojic acid (3 ) indicated that kojic acid might represent a candidate precursor for the development of antimicrobial agents.